Ketahanan Keluarga dalam Perkembangan Moral dan Spiritual Peserta Didik - Nur Faiz Habibah (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2022)
Abstract The moral and spiritual development of students is not directly owned by students from birth, but requires assistance to develop it. The family is the basis for the moral and spiritual formation of students in understanding what is right and what is wrong. This study aims to explain the role of family resilience in developing the moral and spiritual of students. This study uses a qualitative approach, with the location of Jajag Village, Gambiran District, Banyuwangi Regency. Data were collected by observation, interview and analysis methods. Testing the validity of the data is measured using source triangulation techniques, methods, extension of observation time, checking. Data reduction, data display and conclusions in analyzing. Family resilience that is applied in the family environment provides a sense of happiness for students. The ability of students to go through the early childhood phase to adolescence will be easy to pass properly, in accordance with the morals that society expects. The function of family resilience is the basis for students to be able to improve their moral and spiritual development. Support and motivation from the family becomes the spirit of students in improving morally and spiritually.